Forensic Identification Using Dental Restorations: A Radiographic and Material-Based Perspective - Fauziah, Yessy Andriani; Darmadi, Eveline Yulia; Budiharjo, Adrianto; Wahjuningrum, Dian Agustin (Universitas Airlangga, 2025)
Background: Forensic identification is a critical aspect of criminal investigations and disaster victim identification (DVI). Dental records, particularly dental restorations, serve as essential forensic markers due to their resistance to decomposition and environmental conditions. The integration of radiographic imaging and material-based analysis enhances the accuracy of forensic identification, allowing experts to match post-mortem findings with ante-mortem records. Purpose: This literature review aims to explore the role of dental restorations in forensic identification, focusing on the radiographic techniques and material-based forensic analysis used in modern forensic odontology. Reviews: This literature discusses the durability and uniqueness of dental restorations in forensic investigations. Various radiographic techniques, including periapical, panoramic, and cone-beam computed tomography (CBCT) imaging, are examined for their effectiveness in detecting and analyzing restorations. Additionally, the forensic relevance of restorative materials—such as amalgam, composite resins, ceramics, and metal-based prosthetics—is evaluated in cases where conventional soft tissue or DNA-based identification is not feasible. The review also explores technological innovations, including machine learning algorithms and digital forensic methods, that enhance forensic odontology. Conclusion: Dental restorations remain one of the most reliable forensic markers, particularly in challenging identification cases where DNA and soft tissues are compromised. The integration of advanced radiographic imaging and material analysis significantly enhances the precision of forensic identification. Future developments in AI-driven forensic imaging and automated restoration detection will further strengthen forensic odontology as a crucial field in legal and disaster investigations.